Managerial trustworthiness and buybacks - HUANG, Sterling (Institutional Knowledge at Singapore Management University, 2022)
CEO trustworthiness is positively related to long-term excess returns after buyback announcements. When the CEO is trustworthy, statements that the stock is undervalued are more credible. CEO trustworthiness is initially measured by the extent to which people in the county where the company headquarters is located trust each other. Further, the positive impact of trustworthiness on excess returns is higher when the CEO has been a long-term resident of a high-trust county, and correspondingly, trustworthy CEOs are less likely to be accused of financial misreporting. Our conclusions are confirmed when we use alternative measures of trustworthiness such as employee trust and CEO integrity.